MALDI–TOF bacterial subtyping for rapid detection of biomarkers in Staphylococcus aureus from subclinical bovine mastitis - Lopes, Thainara; Fidelis, Carlos E.; Silva, Amanda T.F.; Mota, Rinaldo A.; Rall, Vera L.M. [UNESP]; dos Santos, Marcos V.; Gonçalves, Juliano L. (Oxford University Press (OUP), 2023)
Aims: This study aimed to evaluate matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) bacterial subtyping for the rapid detection of biomarkers in Staphylococcus aureus from subclinical bovine mastitis. Methods and results: A total of 229 S. aureus isolates were obtained from milk samples collected from cows with subclinical mastitis using microbiological culture. Staphylococcus aureus isolates were also submitted to PCR analysis targeting the mecA and mecC genes, which are indicative of methicillin resistance. Confirmation of the species was achieved through MALDI–TOF MS analysis. To analyze antimicrobial resistance patterns, the MALDI BioTyper Compass Explorer and ClinProTools Bruker software were employed, and dendrograms were generated using Bionumerics software. Conclusions: MALDI–TOF MS successfully identified S. aureus at the species level, but no methicillin resistance was observed. Moreover, spectral typing displayed limited similarity when compared to pulsed-field gel electrophoresis (PFGE).
Keywords: biomarkers; MALDI–TOF MS; mastitis; PCR; resistance; Staphylococcus aureus